Investigation of Cryptocarya nigra extracts as a green corrosion inhibitor on mild steel and its phytochemical studies / Mas Faiz Mas Rosemal Hakim - Mas Faiz , Mas Rosemal Hakim (2019)
Three crude extracts; hexane (CNHE), dichloromethane (CNDE) and methanol (CNME) from the bark of Cryptocarya nigra were investigated for their corrosion inhibition properties on mild steel in 1M HCl media. CNDE showed the highest inhibition efficiency for the electrochemical impedance (EIS) and potentiodynamic polarization (PDP) experiments, respectively. Further identification, fractionation and purification of the active compounds from CNDE were analyzed under positive mode using liquid chromatography-mass spectrometer-ion trap-time of flight (LCMS-IT-TOF), column chromatography (CC) and preparative thin layer chromatography (PTLC). Structural elucidation of the seven known compounds named (+)-N-methylisococlaurine 1, atherosperminine-N-oxide 2, atherosperminine 3, 2-hydroxyatherosperminine 4, argentinine 5, (+)-N-methyllaurotetanine 6 and (+)-laurotetanine 7 were successfully accomplished via optical polarimeter, UV-Vis spectrophotometer, FITR, 1D and 2D NMR spectroscopy (COSY, HMBC, HSQC). 1, 3 and 6 were evaluated for their corrosion inhibition potentials and found to be in the ascending order of 1< 3< 6 at their respective optimum concentrations. EIS and PDP experiments showed that 6 reduced the corrosion rate significantly through charge transfer mechanisms. ΔGads values calculated from the Langmuir adsorption isotherm plots for CNDE and 6 suggested that they adsorbed on the mild steel surface dominantly via physisorption mechanism. Scanning electron microscopy micrographs and elemental composition studies confirmed the improvement of the surface morphologies by the formation of protective films over the metal surface.